Tumor necrosis factor-alpha and interleukin-6 in early-onset neonatal sepsis - Prambudi Rukmono; Nani Dharmasetiawani; Warsono Warsono; Yan Wirasti; Eryati Darwin (Indonesian Pediatric Society, 2016)
Background Neonatal sepsis remains a major cause of mortality and morbidity in newborns. Early-onset neonatal sepsis occurs in infants under the age of 72 hours, while late-onset neonatal sepsis occurs in infants over the age of 72 hours and may be due to nosocomial infection. Diagnosing neonatal sepsis is a challenge, as its clinical symptoms are not clear. Corroborating tests include routine blood, C-reactive protein (CRP), serology, tumor necrosis factor-alpha (TNF-Î±), and interleukin-6 (IL-6) examinations.Objective To compare the TNF-Î± and IL-6 levels in patients with proven and unproven early-onset neonatal sepsis (EONS)Methods This case-control study was done in the Perinatology Unit, Abdul Moeloek Hospital, Lampung. Subjects were under the age of 72 hours with risk factors and clinical symptoms of sepsis. They underwent routine blood tests and blood cultures. Infants with positive cultures were considered to have proven sepsis (26 subjects) and infants with negative blood cultures were considered to have unproven sepsis (26 subjects). All subjects underwent serological examinations of TNF-Î± and IL-6.Results There were no differences in the basic characteristics of subjects between the two groups. Levels of TNF-Î± in the sepsis group were significantly higher than in the unproven group [(28.30 vs. 10.96 pg/mL, respectively (P=0.001)]. Furthermore, Il-6 was significantly higher in the proven sepsis group than in the unproven sepsis group [(28.3 vs. 9.69 pg/mL, respectively) (P=0.006)].Conclusion Levels of TNF-alpha and IL-6 are significantly higher in infants with proven than unproven early-onset neonatal sepsis.